Case report: A rare complication after the implantation of a cardiac implantable electronic device: Contralateral pneumothorax with pneumopericardium and pneumomediastinum - Lo, Shao-Wei; Chen, Ju-Yi (Frontiers in Cardiovascular Medicine, 2022)
Cardiac implantable electronic devices (CIED) including pacemakers (PM), implantable cardioverter defibrillators (ICD), and cardiac resynchronized therapy (CRT) have become the mainstay of therapy for many cardiac conditions, consequently drawing attention to the risks and benefits of these procedures. Although CIED implantation is usually a safe procedure, pneumothorax remains an important complication and may contribute to increased morbidity, mortality, length of stay, and hospital costs. On the other hand, pneumopericardium and pneumomediastinum are rare but potentially fatal complications. Accordingly, a high degree of awareness about these complications is important. Pneumothorax almost always occurs on the ipsilateral side of implantation. The development of contralateral pneumothorax is uncommon and may be undetected on an initial chest radiograph. Contralateral pneumothorax with concurrent pneumopericardium and pneumomediastinum is much rarer. We describe a rare case of concurrent right-sided pneumothorax with pneumopericardium and pneumomediastinum after left-sided pacemaker implantation and highlight the risk factors, management, and possible ways to prevent the complications.